Agnes Grey - Brontë, Anne, 1820-1849 (Barnes & Noble classics., 2005)
Written when women and workers generally had few rights in England, Agnes Grey exposes the brutal inequities of the rigid class system in mid-nineteenth century Britain. Agnes comes from a respectable middle-class family, but their financial reverses have forced her to seek work as a governess. Pampered and protected at home, she is unprepared for the harsh reality of a governess's life. At the Bloomfields and later the Murrays, she suffers under the snobbery and sadism of the selfish, self-indulgent upper-class adults and the shrieking insolence of their spoiled children. Worse, the unique social and economic position of a governess, beneath her employers but above their servants, condemns her to a life of loneliness. Less celebrated than her older sisters Charlotte and Emily, Anne Bronte was also less interested in spinning wildly symbolic, romantic tales and more determined to draw realistic images of conditions in Victorian England that need changing.